2014
DOI: 10.1016/j.mod.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical control of notochord morphogenesis by extra-embryonic tissues in mouse embryos

Abstract: Mammalian embryos develop in coordination with extraembryonic tissues, which support embryonic development by implanting embryos into the uterus, supplying nutrition, providing a confined niche, and also providing patterning signals to embryos. Here, we show that in mouse embryos, the expansion of the amniotic cavity (AC), which is formed between embryonic and extraembryonic tissues, provides the mechanical forces required for a type of morphogenetic movement of the notochord known as convergent extension (CE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…Recently, similar movements have also been described during mouse notochord elongation (Yamanaka et al, 2007;Imuta et al, 2014). It was shown that the amniotic cavity provides forces for CE movement necessary for notochord formation, highlighting the importance of extraembryonic tissues as a source of forces to control embryo morphogenesis (Imuta et al, 2014). Additionally, Yamanaka and colleagues used time-lapse imaging to visualize cellular behaviors during notochord formation.…”
Section: From Notochordal Plate Cells On the Embryo's Ventral Surfacementioning
confidence: 83%
“…Recently, similar movements have also been described during mouse notochord elongation (Yamanaka et al, 2007;Imuta et al, 2014). It was shown that the amniotic cavity provides forces for CE movement necessary for notochord formation, highlighting the importance of extraembryonic tissues as a source of forces to control embryo morphogenesis (Imuta et al, 2014). Additionally, Yamanaka and colleagues used time-lapse imaging to visualize cellular behaviors during notochord formation.…”
Section: From Notochordal Plate Cells On the Embryo's Ventral Surfacementioning
confidence: 83%
“…This prompted us to further simplify the situation: instead of an expanding curved three-dimensional surface, we assumed an isotropically expanding two-dimensional plane on which the distance between two arbitrary points increases at a rate proportional to their distance (Fig. 1D; e.g., the distance between two gray circles), as described in our earlier study (13). This situation can also arise in a two-dimensional tissue, like a cell sheet, in which spatially uniform cell proliferation, radial intercalation (16, 17), or cell flattening occurs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A and B). We showed that in contrast to notochord elongation in other species, which is induced by active cell movement (1, 2, 11), elongation of the mouse notochord is driven, at least in part, by the passive mechanical effects of embryonic expansion (13). Because the expansion of the embryo is almost isotropic, like a spherically expanding balloon, the direction of the extrinsic forces provided from the expanding embryo are expected to be unbiased and uncorrelated with the direction of notochord elongation (Fig.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations